Mentally Disabled Sex Education through Powerpoint Media - Nurhusni Nurhusni; Fatmawati Fatmawati (STAI Miftahul Ula Nganjuk, 2019)
This research is motivated by problems about four students who experience problems in self-development, especially in understanding adolescent sex education. Based on observations, students do not understand about adolescent sex, so that makes students not aware of the physical and biological changes that occur in him. The purpose of this study is to improve children's understanding of adolescent sex education through powerpoint media. The research method used was classroom action research consisting of two cycles. Each cycle consists of four face-to-face meetings that are carried out in several stages, namely planning, implementing actions, observing, and reflecting. Data collection techniques used were observation, documentation, and tests. The results of this study indicate that the learning process of sex education through power points for Grade VII mentally retarded persons. Children's understanding of adolescent sex education has increased through the use of powerpoint media. So it can be concluded that the implementation of sex education learning can be increased through powerpoint media for mild mental retardation.